Recurrent-and-Parallel GMDH Algorithms for High-Performance Computing - Stepashko, V.S.; Yefimenko, S.M.; Pavlov, A.V. (Управляющие системы и машины, 2019)
The paper presents the conception, theoretical grounds and mathematical tools for designing high-performance searching and iterative GMDH algorithms on the basis of recurrent-and-parallel computing for modelling and prediction of complex processes. Its effectiveness is experimentally tested. Intelligent information technology for inductive modeling of complex processes on the basis of recurrent-and-parallel computing is constructed.